Perancangan Alat Pengolahan Sampah Organik Berbasis Internet of Things (IoT) untuk Produksi Gas Metana dan Pupuk Kompos - Jastin; Vincen; Habib Bahy Hussein; Bonni Saputra; Sabariman Sabariman; Andik Yulianto (Universitas Internasional Batam, 2026)
This paper presents the design of an Internet of Things (IoT)-based organic waste processing device to produce methane gas and compost. The system uses a large sealed plastic container fitted with a biogas nanometer gauge on the lid and an ESP32 microcontroller for data acquisition. A capacitive soil moisture sensor measures the moisture of decomposed organic material, while an MQ-4 gas sensor monitors methane concentration inside a separate 5-liter plastic storage tank. Organic waste is fermented naturally, and gas is transferred manually through establishing valves while the pressure reaches a described threshold. All sensor information are dispatched to the Blynk cellular software for real-time tracking and visualization. This low-price answer gives a realistic technique to changing family natural waste into renewable power and natural fertilizer.